ARTIFICIAL INTELLIGENCE IN THE CASE-LAW OF THE EUROPEAN COURT OF HUMAN RIGHTS - KUTOVYI, OLEKSANDR; BURMA, SERGII (Ehrlich's Journal, 2025)
This article examines the impact of algorithmic and computer systems, methods, and artificial intelligence (AI) software on the judicial practice of the European Court of Human Rights (ECtHR), particularly the challenges and opportunities arising from the technological development of society. The article analyzes the ECtHR’s practice regarding references to AI systems and tools in the text of judicial decisions, related issues concerning the implementation of human rights, as well as identified and potential human rights violations. Special attention is given to issues of privacy, the protection and processing of personal data, and control over their use. These issues are particularly pressing in cases involving the automatic processing of data, algorithmic decisions, and the loss of control over personal data, which may violate the right to privacy under Article 8 of the European Convention on Human Rights and Fundamental Freedoms. The article explores specific ECtHR decisions where AI is mentioned directly or indirectly and identifies key issues arising in judicial practice. With the entry into force of the Artificial Intelligence Act (AI Act), Regulation (EU) 2024/1689 of the European Parliament and of the Council of 13 June 2024, it can be expected that the use of AI will become even more relevant for the development of judicial practice, as AI technologies increasingly impact democratic processes and fundamental human rights. Therefore, further research on judicial practice and normative initiatives aimed at ensuring human rights in the context of digitalization is crucial for the development of legal standards for the use of AI. The article emphasizes that although existing ECtHR decisions do not directly address the use of AI, they provide important guidelines for the development of legal standards that can be adapted to new realities, particularly for the protection of personal data and privacy guarantees in the digital environment.